2021
DOI: 10.7759/cureus.15994
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management in Breast Cancer Patients: A Multidisciplinary Approach

Abstract: Pain is a significant problem and is one of the most invalidating symptoms in breast cancer (BC) patients that would negatively affect the functional status and the Quality of Life (QoL). Pain management in BC patients requires thorough patient evaluation and critical assessment of pain. The actual cause for the pain must be recognized, so management can be tailored to each patient. This review aims to discuss various treatment modalities employed for effectively managing pain in BC patients.Pharmacotherapy ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…The results of this study showed that self-management training is significant in decreasing salivary cortisol in the intervention group. This is similar with other research reporting that education and training relaxation programs as self-management, including pain management, significantly decreased cortisol in patients with stage 0-stage 3 cancer without metastasis (Alhazmi et al, 2021). Breathing relaxation exercises help improve the patient's ability to reduce tension and increase the patient's ability to relax, thus decreasing stress and blocking cortisol through the HPA axis system (Ramírez-Expósito et al, 2021;Soetrisno et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study showed that self-management training is significant in decreasing salivary cortisol in the intervention group. This is similar with other research reporting that education and training relaxation programs as self-management, including pain management, significantly decreased cortisol in patients with stage 0-stage 3 cancer without metastasis (Alhazmi et al, 2021). Breathing relaxation exercises help improve the patient's ability to reduce tension and increase the patient's ability to relax, thus decreasing stress and blocking cortisol through the HPA axis system (Ramírez-Expósito et al, 2021;Soetrisno et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…The intensity of pain, as reported by the patient, is regarded as the gold standard for routine pain assessment. Therefore, effective pain management relies on consistent screening for early detection of pain, accurate description of the pain's characteristics such as onset, duration (acute or chronic), intensity, location, severity, underlying pathophysiology, association with treatment, breakthrough pain, and more ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of pain can be due to the release of inflammatory mediators, invasion into other tissues (bone, muscle, nerve structures). Similarly, treatments potentiate pain, including surgery, radiotherapy, chemotherapy, immunotherapy, and hormone therapy [6,7]. Women with hormone receptor-positive breast cancer usually take hormone therapy to reduce the risk of a relapse.…”
Section: Introductionmentioning
confidence: 99%